Hemicellulose-Derived Oligosaccharides: Emerging Prebiotics in Disease Alleviation - Jana, Uttam Kumar; Kango, Naveen; Pletschke, Brett (Frontiers in Nutrition, 2021)
The gut microbiota in the human body is an important component that plays a pivotal role in the host’s ability to prevent diseases and recover from these. If the human microbiome changes for any reason, it affects the overall functioning of the host. Healthy and vigorous gut microbiota require dietary fiber supplementation. Recently, oligosaccharides have been found to play a significant role in microbiota modulation. Several such oligosaccharides, i.e. xylooligosaccharides, mannooligosaccharides and arabino-xylooligosaccharides are derived from hemicellulosic macromolecules such as xylan, mannan and arabino-xylan, respectively. These oligosaccharides serve as substrates for the probiotic production of health promoting substances (short-chain fatty acids, branched chain amino acids etc.), which confer a variety of health benefits, including prevention of some dreaded diseases. Among hemicellulose derived oligosaccharides (HDOs), xylooligosaccharides have been largely explored, whereas studies on mannooligosaccharides and arabino-xylooligosaccharides are currently underway. HDOs, upon ingestion, help reduce morbidities by lowering populations of harmful or pathogenic bacteria. The ATP-binding cassette (ABC) transporters are mainly utilized for oligosaccharide uptake in the probiotics. Butyrate generated by the selective fermentation of oligosaccharides, along with other short chain fatty acids, reduce gut inflammation. Overall, oligosaccharides derived from hemicelluloses show similar potential as conventional prebiotics and can be supplemented as functional foods. The present review summarizes the role of HDOs in the alleviation of autoimmune diseases (inflammatory bowel disease, Crohn’s disease), diabetes, urinary tract infection, cardiovascular diseases and anti-microbial resistance (AMR) through the modulation of gut microbiota. The mechanism of oligosaccharide utilization and disease mitigation is also explained.